Prescribing drugs of dependence in dentistry: a review of legal and regulatory considerations. (9th July 2021) - Johnstone, M; Teoh, L; Holden, ACL
ABSTRACT: The misuse of drugs of dependence is a major public health issue in Australia, and prescribing of these medications by dentists has increased in recent years. While there has been much focus on the appropriate indications and clinical use of these medicines in dental practice, the legal requirements of prescribing are equally important. Dental practitioners need to be aware of their legal obligations, as inappropriate prescription practices may lead to regulatory or criminal prosecution. Although dentists hold registration through the National Scheme and there is nationally standardised scheduling of drugs in Australia, the legislation governing drug laws differs for each state and territory, especially when prescribing drugs of dependence. This article summarises the legislation governing the prescription of drugs of dependence in Australia that is relevant to dental practice, providing insights into how dentists might contribute to the appropriate, safe and legal use and management of these medications.